Safinah an-Najat: Kitab Kuning Mengenai Fikih bagi Santri Pemula di Indonesia - Sumarsana, Utju (ASPENSI in Bandung, Indonesia, 2009)
ABSTRACT: The Yellow Old Book or âKitab Kuningâ, as the product of cultural heritage in the past, cannot be separated from the Indonesian society. In some aspects, this book could answer many religious and daily problems at certain time. However, the content of this book could ispire current situation. It is interesting to note that most of the yellow old books that are learnt in the Islamic boarding school (Pesantren) in Indonesia consist of Islamic law, especially on the âfiqhâ or regulation for praying to Allah SWT. I believed that all of these kind of Islamic boarding schools in Indonesia considere the yellow old books as one their learning materials. Accordingly, âSafinah an-Najatâ is one of the yellow old books that is used as reference book for these Islamic boarding schools. This book is famous among them as a beginning book to be learnt about âfiqhâ by their students. This article describing the structural content of âSafinah an-Najatâ book. I noted that this book consists of some important concepts and the implementation of the Islamic regulation, such as: (1) the Islamic foundation law, the basic of believing, theology, maturity, cleanse, praying, mortal remains procession, tithe and fasting; (2) the meaning of âla ilaha illallahâ statement and adultness; and (3) the compulsory daily prayer. Based on the number of articles in those book of âSafinah an-Najatâ, there are 29 articles (43.3%) of âshalatâ (Moslem praying), 17 articles (25.4%) of fasting, 6 articles (8.9%) of mortal remains procession, 2 articles of tithe, and 1 article (1.5%) for each of Islamic foundation law, the basic believing, theology and adultness. So it is absolutely clear that âSafinah an-Najatâ is a book to introduce the implementation on individual praying obligation rather than the social obligation of Islamic ummah. Key words:Â yellow old book, Safinah book, the concept and implementation of the Islamic regulation, and Islamic boarding school studentsâ view on the âfiqhâ in Indonesia.About the Author: Drs. Utju Sumarsana, M.Si. adalah Mahasiswa S3 pada Program Studi Filologi Pascasarjana UNPAD (Universitas Padjadjaran) Bandung; dan sekarang menjabat sebagai Kepala Subdit Pembelajaran, Direktorat Pembinaan TK dan SD, Ditjen Mandikdasmen, Depdiknas RI di Jakarta. Dilahirkan di Kuningan, Jawa Barat, pada 22 Agustus 1955. Menyelesaikan pendidikan Sarjana (Drs.) dari Jurusan Pendidikan Ekonomi IKIP (Institut Keguruan dan Ilmu Pendidikan) Jakarta tahun 1980; dan pendidikan S2 (M.Si.) dari Program Studi Administrasi Publik Pascasarjana UGM (Universitas Gadjah Mada) Yogyakarta tahun 1990. Banyak mengikuti seminar, baik di dalam maupun di luar negeri. Untuk kepentingan akademik, beliau boleh dihubungi dengan alamat rumah: Jalan Masjid II No.132, Sudimara Selatan, Tangerang, Banten. E-mail: utju_sumarsana@yahoo.co.idHow to cite this article? Sumarsana, Utju. (2009). âSafinah an-Najat: Kitab Kuning Mengenai Fikih bagi Santri Pemula di Indonesiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.2, No.1 [Mei], pp.15-30. Bandung, Indonesia: Minda Masagi Press, UPI Bandung, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (March 11, 2009); Revised (April 24, 2009); and Published (May 20, 2009).